High seroprevalence of antibodies against Kaposi’s sarcoma-associated herpesvirus (KSHV) among HIV-1-infected children and adolescents in a non-endemic population - Feiterna-Sperling, Cornelia; Buchholz, Bernd (Medical microbiology and immunology, 2016)
Human herpesvirus-8 (HHV-8) is the etiological agent of Kaposi’s sarcoma (KS), which primarily affects human immunodeficiency virus (HIV)-infected adults with advanced immunodeficiency. Currently, only limited prevalence data for HHV-8 infection in HIV-infected children living in non-endemic areas are available. This multicenter cross-sectional study was conducted in four university hospitals in Germany specializing in pediatric HIV care. Stored serum specimens obtained from 207 vertically HIV-1-infected children and adolescents were tested for antibodies against lytic and latent HHV-8 antigens. Logistic regression was used to assess independent risk factors associated with HHV-8 seropositivity. The overall HHV-8 seroprevalence was 24.6 % (n = 51/207) without significant differences related to sex, age, or ethnicity. In univariate analysis, HHV-8 seropositivity was significantly associated with a child having being born outside Germany, maternal origin from sub-Saharan Africa, a history of breastfeeding, CDC immunologic category 3, and deferred initiation of antiretroviral therapy (>24 months of age). In multivariate analysis, a child’s birth outside Germany was the only significant risk factor for HHV-8 seropositivity (odds ratio 3.98; 95 % confidence interval 1.27-12.42). HHV-8-associated malignancies were uncommon; only one patient had a history of KS. Serum specimen of vertically HIV-infected children and adolescents living in Germany showed a high HHV-8 seroprevalence. These findings suggest that primary HHV-8 infection—a risk factor for KS and other HHV-8-associated malignancies—occurs early in life. Thus, management of perinatally HIV-infected children should include testing for HHV-8 coinfection and should consider future risks of HHV-8-associated malignancies.
Gesehen am 08.07.2019